RNAlater facilitates remote sampling of aquaculture Atlantic salmon liver for proteomic analysis. Issue 6 (3rd October 2022) - Rusu, Anca G.; Broadbent, James A.; Wade, Nicholas M.; Simon, Cedric J.; Rombenso, Artur N.; Osborne, Simone A.; Mendoza‐Porras, Omar
Abstract: During sample collection and transport, high‐quality nucleic acids, proteins and metabolites are preserved by snap‐freezing (SF) samples in liquid nitrogen or dry ice. In remote aquaculture facilities, SF materials are not readily available and can be hazardous during sampling and transport. RNAlater is widely used in aquaculture for transcriptome studies, but its effect on proteome stability needs further investigation. Here, we used proteomics to demonstrate that RNAlater (RL) preserved liver samples similarly to SF samples. Additionally, 69 proteins (∼2.6%) comprising ribosomal proteins, transcription cofactors, translational factors, proteases and transmembrane proteins were significantly less abundant in the RL proteome. These proteins are expected to be denatured by RL and are cellular components of ribosomes and nucleosomes and involved in proteolysis, transcription and translation. We also demonstrated that RL did not influence abundance of important proteins originally identified in liver samples from salmon reared under heat stress, hypoxia or specific feeding regimes. These findings suggest that preserving samples in RL is suitable for proteomics and offer a safer and effective preservation technology for use in remote aquaculture locations. Graphical Abstract: Proteomes of similar sizes were obtained in samples preserved by snap‐freezing or RNAlater. Proteins involved in transcriptional and translational machinery were affected in RNAlater stored samples. Abundance of published markers for heat and oxidative stress was not affected by snap‐freezing or RNAlater.